The Problem-Based Learning Model in Mathematics Subjects by Controlling the Critical Thinking Ability of Elementary School Students - Ni Nyoman Ayu Purnama Dewi; Gusti Ngurah Sastra Agustika (Universitas Pendidikan Ganesha, 2023)
The low competence of knowledge in mathematics subjects is due to the need for appropriate learning models. It refers more to the theories in learning materials rather than relating them to real life or students' daily lives. This study aimed to analyze the effect of the Problem-Based Learning model on the competence of mathematical knowledge by controlling the critical thinking skills of fifth-grade elementary school students. This study used a quasi-experimental design with the Nonequivalent Control Group Design and the Single Factor Independent Group Design With the Use Of Covariate data analysis design. The population in this study was 194 students from 3 different public schools. The sample was determined using the cluster random sampling technique. Previously the population was equalized using the Anava test. Methods of data collection using tests in the form of descriptions and research data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques using Anakova Test. The results of the hypothesis analysis obtained that the Problem-Based Learning model affected Students' Mathematical Knowledge Competence even though it had been controlled for the Critical Thinking Ability of Grade V Students in elementary schools. It was concluded that the Problem-Based Learning model could improve Students' Mathematical Knowledge Competence.